Tectono-Stratigraphic Implications in Extending the Panjal Thrust, West of The Hazara-Kashmir Syntaxis - Tahirkheli, R. A. Khan; Riaz, Mohammad (Journal of Himalayan Earth Sciences, 1991)
The Panjal Thrust (PT) is one of the principal tectonic scars of the Lesser Himalayan domain in Kashmir. Its type section is located in the Panjal Range from where it extends northeastwards along the eastern flank of the Hazara-Kashmir syntaxis and terminates at its apex. In the Panjal Thrust the Precambrian Salkhalas thrust over the Permo-Triassic Panjal Group. This tectonostratigraphic setup is retained by this thrust throughout its course in Kashmir. During recent years, some geologists have extended this thrust west of the syntaxis through Galiat, Abbottabad, Gandghar Range and terminated it across the Indus in the Attock-Cherat Range. The tectono-stratigraphic and lithostratigraphic frames of these sections are not akin to the ones displayed in the Panjal Thrust sections in Kashmir. This controversial aspect of the Panjal Thrust has been studied to ascertain whether the western counterparts of the Panjal Thrust west of the Hazara-Kashmir syntaxis has any justification to be correlated with its tectono-stratigraphic net displayed in Kashmir.